Induced Pluripotent Stem Cells from Individuals with Recessive Dystrophic Epidermolysis Bullosa - Tolar, Jakub (2010)
Recessive dystrophic epidermolysis bullosa (RDEB) is an inherited blistering skin disorder caused by mutations in the COL7A1 gene-encoding type VII collagen (Col7), the major component of anchoring fibrils at the dermal-epidermal junction. Individuals with RDEB develop painful blisters and mucosal erosions, and currently there are no effective forms of therapy. Nevertheless, some advances in patient therapy are being made, and cell-based therapies with mesenchymal and hematopoietic cells have shown promise in early clinical trials. To establish a foundation for personalized, gene-corrected, patient-specific cell transfer, we generated induced pluripotent stem cells from three subjects with RDEB (RDEB iPS cells). We found that Col7 was not required for stem cell renewal and that RDEB iPS cells could be differentiated to both hematopoietic and non-hematopoietic lineages. The specific epigenetic profile associated with de-differentiation of RDEB fibroblasts and keratinocytes into RDEB iPS cells was similar to that observed in wild-type iPS cells. Importantly, human wild-type and RDEB iPS cells differentiated in vivo into structures resembling skin. Gene-corrected RDEB iPS cells expressed Col7. These data identify the potential of RDEB iPS cells to generate autologous hematopoietic grafts and skin cells with the inherent capacity to treat the skin and mucosal erosions that typify this genodermatosis.